Fibrous protein-based biomaterials (silk, keratin, elastin, and resilin proteins) for tissue regeneration and repair - Costa, F.; Marques da Silva Lourenco, Raquel de Jesus; Boccaccini, Aldo R. (Peptides and Proteins as Biomaterials for Tissue Regeneration and Repair, 2018)
Tissue scaffolds are essential in tissue engineering approaches as they provide a tissue-mimicking environment for cells, with the aim to promote cell proliferation, cell differentiation, and tissue regeneration. To mimic better the microenvironment of native tissues, numerous techniques, and biomaterials have emerged in recent years. Among them, hydrogels formed from self-assembled biopolymer networks are particularly interesting. This chapter reviews the fabrication and use of fibrous protein-based hydrogels, with an emphasis on silk, keratin, elastin, and resilin proteins. Hydrogels formed by these proteins show structural, chemical, and mechanical similarities with the extracellular matrix of human tissues, typically exhibiting biological compatibility, and they can trigger specific cellular responses. In addition, these hydrogels can be degraded in the body by proteolytic enzymes. For these reasons, fibrous protein hydrogels are versatile materials for tissue engineering.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Biomaterials; Cell-encapsulation; Fibrous-proteins; Hydrogels